Flatband nonlinear metasurface for broad-angle photon-pair generation - Yuxin Jiang; Jihua Zhang; Jinyong Ma; Dragomir N. Neshev; Andrey A. Sukhorukov (APL Quantum, 2025)
Current nonlinear metasurface photon-pair sources face limitations in angular emission range and uniformity due to optical resonance dispersion, potentially hindering their application in quantum imaging, which demands broad-angle emission for a wide field of view and high resolution. Here, we propose a broad-angle photon-pair source using flatband engineering. We demonstrate that tailored partially etched patterns in a lithium niobate metasurface can facilitate a flatband across a wide transverse wavevector range (±0.2 rad/μm) around a 1573 nm wavelength. The flatband metasurface supports enhanced photon-pair generation at a simulated rate of 539 Hz/mW within a cone of 3° apex angle relative to the pump propagation, which is an order of magnitude broader than previously reported metasurfaces. This general approach is also scalable to other wavelengths, opening new possibilities for compact entangled photon-pair sources in quantum imaging.